2013
DOI: 10.1016/j.rser.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy production in Central America: Integration of sweet sorghum into sugar mills

Abstract: Central America Sweet sorghum Electricity Ethanol Sugar millsThis paper aims to evaluate the potential for electricity and ethanol production in Central America using sweet sorghum as an energy crop. Three scenarios were built to analyse sweet sorghum production in terms of the land where it can be cultivated: cropland, sugarcane land in fallow and land in continuous production (intercropping system). The land under permanent crops was not considered for this evaluation. We propose the integration of sweet sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It can be a supplementary feedstock to the sugar mills operating with the distilleries in the off season (2 mo), development of average revenue of US$3 million for a crushing rate of 6500 t d −1 can be achieved in dryland situations. Several studies have highlighted the potential of sweet sorghum for ethanol production (Srinivasarao et al, 2009), and it was reported as a viable feedstock for electricity production (Cutz et al, 2013).…”
Section: Bioethanol From Sorghum: Current Scenariomentioning
confidence: 99%
“…It can be a supplementary feedstock to the sugar mills operating with the distilleries in the off season (2 mo), development of average revenue of US$3 million for a crushing rate of 6500 t d −1 can be achieved in dryland situations. Several studies have highlighted the potential of sweet sorghum for ethanol production (Srinivasarao et al, 2009), and it was reported as a viable feedstock for electricity production (Cutz et al, 2013).…”
Section: Bioethanol From Sorghum: Current Scenariomentioning
confidence: 99%
“…Renewable energy is a potential solution to increasing global energy demand, climatic change, and ecological challenges [19], but must be environmentally, socially, and economically sustainable if its benefits are to be fully recognized [18]. However, despite the advantages of renewable energy, some Latin American countries are still highly dependent on fossil fuels (from 40%-80% of total energy demand) or other forms of energy production, mainly hydroelectric power (11%) [6,7].…”
Section: Renewable Energy and Biomass In Latin Americamentioning
confidence: 99%
“…Biomass as a renewable energy resource is important, however, some authors have pointed out that this energy must be used smartly [26,27]. Cooking and heating in developing countries, such as in Central America [7], utilizes one-third of the biomass produced around the world [18]. Meanwhile, developed countries utilize biomass in industrial applications, such as in the heating, power, and road transportation sectors, and for heating purposes in the private sector [1].…”
Section: Renewable Energy and Biomass In Latin Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Sweet sorghum, which was mentioned five times, is a variant of grain sorghum that contains a much higher percentage of sugars and is often processed much like sugar cane (Cutz et al 2013). Like sugar cane, however, it also has problematic bagasse.…”
Section: Sweet Sorghummentioning
confidence: 99%